Glaucoma "landscape" in Russia, CIS and Eastern European countries: what has changed over 15 years? - A.Yu. Brezhnev; E.A. Egorov; V.P. Erichev; A.V. Kuroyedov; P.Ch. Zavadskiy; M. Bozic; N.N. Voronova; M.F. Dzhumova; N.V. Ivanova; T.A. Imshenetskaya; T.G. Kamenskikh; L.N. Marchenko; et al. (РМЖ "Клиническая офтальмология")
A.Yu. Brezhnev1, E.A. Egorov2, V.P. Erichev3, A.V. Kuroedov2,4, P.Ch. Zavadsky5, M. Bozic6, N.N. Voronova7, M.F. Dzhumova8, N.V. Ivanova7, T.A. Imshenetskaya9, T.G. Kamenskikh10, O.I. Lebedev11, L.N. Marchenko8, A.L. Onishchenko12, N.A. Sobyanin13, V.F. Ekgardt14 1Kursk State Medical University, Kursk, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation 3Krasnov Research Institute of Eye Diseases, Moscow, Russian Federation 4P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation 5LLC "Ophthalmological Center of Karelia", Petrozavodsk, Russian Federation 6University Eye Clinic, University of Belgrade, Belgrade, Serbia 7V.I. Vernadsky Crimean Federal University, Simferopol, Russian Federation 8Belarusian State Medical University, Minsk, Belarus 9Belarusian Medical Academy of Post-Diploma Education, Minsk, Belarus 10V.I. Razumovskiy Saratov State Medical University, Saratov, Russian Federation 11Omsk State Medical University, Omsk, Russian Federation 12Novokuznetsk State Institute for Advanced medical Education — Branch of Russian Medical Academy of Continuous Professional Education, Novokuznetsk, Russian Federation 13F.Kh. Gral City Clinical Hospital No. 2, Perm, Russian Federation 14South Ural State Medical University, Chelyabinsk, Russian Federation Aim: to assess the changes in clinical and epidemiological characteristics, diagnostic and treatment options of primary open-angle glaucoma (POAG) in the Russian Federation and multiple near- and far-abroad countries over the period of 2005–2020. Patients and Methods: the final protocol of this retrospective multi-center research and clinical study included 289 patients with POAG from 7 states (Russia, Belarus, Serbia, Moldova, Kyrgyzstan, Slovakia, and Slovenia). The authors analyzed the methods used for establishing POAP diagnosis, clinical and demographic patient characteristics (gender, age and place of residence), as well as the process of glaucoma development (age of onset, disease duration and stages, intraocular pressure, ocular hypotensive medications, and the used laser and surgical procedures). All patients were divided into four groups depending on the time of making the initial diagnosis: 2004–2005, 2009–2010, 2014–2015, 2019–2020. Results: tonometry with Maklakov and Goldmann tonometers is still considered the gold standard for measuring intraocular pressure (IOP) (95% of cases). The percentage of pneumotonometry increased from 40% in 2005 to 60% in 2020. Approximately a third of clinics are still using electronic tonography as a supplementary method. Static automated perimetry is a basic tool for diagnosis and follow-up of patients with POAG (more than 95% of cases). Manual kinetic perimetry (Foerster's perimetry) is used in less than 10% of cases. Ophthalmoscopy (direct and binocular) was involved in the diagnostic process in all clinics and in all cases. The range of instrumental visualization technologies includes optical coherence tomography (OCT), Heidelberg Retina Tomography (HRT), and scanning laser polarimetry. Currently, OCT is utilized in 90% of clinics. It was found out that in 2005 the standard of initial POAG diagnosis encompassed a set of Maklakov/Goldmann tonometry, ophthalmoscopy and kinetic perimetry. In 2020, this list includes Maklakov/Goldmann tonometry, pneumotonometry as a supplemental tool, static automated perimetry, ophthalmoscopy and OCT. The percentage of newly diagnosed POAG at the early stage has increased twofold over the past 15 years (from 20% in 2005 to 38% in 2020). The mean age of patients at the time of initial POAG diagnosis in 2005 was 62 (52; 67) years, in 2020 — 65 (50; 70) years, respectively (р=0.694). The proportion of prostaglandins in medication therapy increased by 20% over the past 15 years, while the proportion of beta-blockers reduced by the same percentage. The use of cholinomimetic drugs was almost discontinued. The total number of glaucoma laser surgeries has grown, and in the last decade the top priority has been given to selective laser trabeculoplasty, while the share of argon laser trabeculoplasty has decreased by 10%. The rate of primary glaucoma surgeries (trabeculectomy) keeps going down. Conclusion: a gradual and consistent implementation of high-tech diagnostic methods (static automated perimetry and OCT) in the routine practice occurred over 2005–2020. Also, there was a clear trend in more extensive use of objective data. The evolution of pharmaceutical "landscape" in the disease management is associated with an increasing proportion of more effective and safe drugs (prostaglandin analogues) and a diminishing role of beta-blockers as drugs of choice for starting therapy. The share of glaucoma surgeries as a starting strategy of POAG management was running down steadily from 2005 to 2010. Keywords: glaucoma, intraocular pressure, tonometry, perimetry, optical coherence tomography, trabeculectomy. For citation: Brezhnev A.Yu., Egorov E.A., Erichev V.P. et al. Glaucoma "landscape" in Russia, CIS and Eastern European countries: what has changed over 15 years? Russian Journal of Clinical Ophthalmology. 2023;23(2):73–79 (in Russ.). DOI: 10.32364/2311-7729-2023-23-2-73-79.